2006
DOI: 10.1111/j.1439-0396.2006.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactoferrin on selected immune system parameters and the gastrointestinal morphology in growing calves

Abstract: Summary Lactoferrin (LF) is a cationic iron‐binding glycoprotein that is abundantly expressed and secreted from glandular epithelial cells and a prominent component of the secondary granules of polymorphonuclear neutrophils. Various in vitro and in vivo experiments demonstrate anti‐microbial, ‐viral, ‐mycotic and ‐inflammatory effects of LF, associated with modulations of the immune system. Effects of oral administered LF on selected immune system parameters were studied in calves. Five calves were fed LF begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…bLf has shown beneficial effects when tested in patients with cancer [24][25][26], and some studies have shown that Lf can promote wound healing and bone growth [5]. bLf showed an immunostimulant effect in calves [27,28], chickens [29], and fishes [30,31]. To explain the physiological effects of bLf, it has been analyzed its bodily distribution in rodents and pigs.…”
Section: Introductionmentioning
confidence: 99%
“…bLf has shown beneficial effects when tested in patients with cancer [24][25][26], and some studies have shown that Lf can promote wound healing and bone growth [5]. bLf showed an immunostimulant effect in calves [27,28], chickens [29], and fishes [30,31]. To explain the physiological effects of bLf, it has been analyzed its bodily distribution in rodents and pigs.…”
Section: Introductionmentioning
confidence: 99%
“…4 Figure 1 reviews the wide range of actions attributed to LF. The ways that LF prevent NEC include: a) its role in host defense against pathogens, 17,18 b) its immuno-modulatory and anti-inflammatory effects, 12,16,19,20 c) its regulation of intestinal cell growth, 9,21,22 and d) its biochemical actions that include ferric iron transport, 23,24 enzymatic activity, 25,26 and nuclear binding and initiation of transcription. 18,27,28 …”
Section: Biochemical Physiologic and Immunologic Characteristics Of Lfmentioning
confidence: 99%
“…12 Human LF enabled B cells from normal newborn and adult immuno-deficient CBA/N mice to present antigen to an antigen-specific Thelper type 2 (Th2) cell line. 12 ◆ LF given orally to calves increases the size of Peyer's patches in the ileum and blood levels of immunoglobulin G. 54 Neonatal rats feed rhLF and Lactobacillus GG compared to LGG alone had an accelerated appearance of 'domed villi', the precursors of Peyer's patches. 15 This finding may result in increased IgA secretion into the intestinal lumen.…”
mentioning
confidence: 99%
“…4 Figure 1 reviews the wide range of actions attributed to LF. The ways that LF prevent NEC include: a) its role in host defense against pathogens, 17,18 b) its immuno-modulatory and anti-inflammatory effects, 12,16,19,20 c) its regulation of intestinal cell growth, 9,21,22 and d) its biochemical actions that include ferric iron transport, 23,24 enzymatic activity, 25,26 and nuclear binding and initiation of transcription. 18,27,28 The pathophysiology of NEC is complex, but several factors are accepted as effectors of the disease.…”
mentioning
confidence: 99%